Margin processes sculpting a land-detached canyon-channel system: the Gollum Channel System in the Porcupine Seabight - Verweirder, L.; Van Rooij, D.; Georgiopoulou, A. (Frontiers in Earth Science, 2023)
The land-detached Gollum Channel System (GCS) is one of very few large-scale canyon-channel systems on the Northwest European margin and thought to be of high importance in both along-slope and downslope sediment transport processes in the Porcupine Seabight basin. It is, however, unknown when this system was formed and how active it has been throughout its evolution, making it difficult to assess its regional impact. Here, using well data integrated with airgun seismic reflection data, a seismic stratigraphy (Cretaceous to present) is built for the GCS for the first time. We find that, contrary to what was thought before, the GCS was formed before Quaternary glaciations occupied the continental shelf and its origin is tentatively associated to a phase of Northeast Atlantic margin tilting in the early Pliocene. Each of the channels that make up the GCS was initiated by incision from erosive downslope gravity flows originating on the Celtic Sea Shelf. Gravity flows from Quaternary glacial processes reused the channels and mostly bypassed the upper slope or contributed to the channel fill, though some flows were capable of erosion of existing channel flanks and incision of several smaller channels. Additionally, we show that this margin was incised by erosive gravity flows on several occasions through time and that these incisions seem to follow preferential pathways. Interaction with along-slope bottom currents from the start of the Quaternary onwards was crucial to distribute sediments and nutrients to sediment drifts and cold-water coral mounds further north (downstream) along the Irish margin.